W.A. Croffut papers - Croffut, W. A. (William Augustus), 1835-1915.; Croffut, W. A. (William Augustus), 1835-1915.; Hitchcock, Ethan Allen, 1798-1870.; Robbins, Henry Alfred, 1839-1911.; Anti-Imperialist League (Washington, D.C.).
Correspondence, journals, minutes of meetings, writings, printed matter, scrapbooks, and other papers pertaining primarily to Croffut's publications and to his activities with the Anti-Imperialist League (Washington, D.C.) and other league branches. Subjects include William Jennings Bryan's candidacy in the presidential campaign of 1900; opposition to American annexation of the Philippines following the Spanish-American War in 1898 and to British actions against the Boers (Afrikaners) during the South African War, 1899-1902; and the World's Columbian Exposition, Chicago, Ill., in 1893. Includes minutes and other records concerning the founding and operation of the Anti-Imperialist League (Washington, D.C.); journals of Henry Alfred Robbins containing accounts of his travels in Europe during the 1870's and information concerning medical practices in Europe; an autograph book and autographs including a John Quincy Adams letter (April 15, no year) and Jefferson Davis note (1853); and material pertaining to George Washington. Correspondents include George S. Boutwell, William Jennings Bryan, Elwood S. Corser, Samuel Gompers, John William Hayes, John B. Henderson, Patrick O'Farrell, Carl Schurz, Bertrand Shadwell, Charles A. Towne, George W. Van Siclen, Erving Winslow, and Croffut's wife, Bessie B. Croffut.
The Ethan Allen Hitchcock File consists of Hitchcock's memoir used for the book, Fifty years in Camp and Field; Diary of Major-General Ethan Allen Hitchcock, edited by Croffut (1909); copies of Hitchcock correspondence along with biographical material; copies of correspondence with Sophia Peabody Hawthorne; Croffut's "Now I Recollect"--"Souvenirs of the Sanctum: Lincoln as I Saw Him" (printed 1943) and other Croffut family writings; and other papers.
Author, editor, and poet.
Collection material in English, with Spanish.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Adams, John Quincy, -- 1767-1848 -- Correspondence; Boutwell, George S. -- 1818-1905 -- Correspondence; Bryan, William Jennings, -- 1860-1925.; Bryan, William Jennings, -- 1860-1925 -- Correspondence; Corser, Elwood S. -- 1835-1903 -- Correspondence; Croffut, Bessie B., -- 1861-1935 -- Correspondence; Davis, Jefferson, -- 1808-1889.; Gompers, Samuel, -- 1850-1924.; Hawthorne, Sophia Peabody, -- 1809-1871 -- Correspondence; Hayes, John William, -- 1854-1942 -- Correspondence; Henderson, John B. -- 1826-1913 -- Correspondence; Hitchcock, Ethan Allen, -- 1798-1870.; Lincoln, Abraham, -- 1809-1865.; O'Farrell, Patrick, -- 1832-1902 -- Correspondence; Schurz, Carl, -- 1829-1906 -- Correspondence; Shadwell, Bertrand -- Correspondence; Towne, Charles A. -- 1858-1928 -- Correspondence; Van Siclen, George W. -- 1840-1903.; Washington, George, -- 1732-1799.; Winslow, Erving, -- 1839-1922 -- Correspondence; Croffut family; United States. -- Army -- Military life; Anti-Imperialist League (Washington, D.C.); Afrikaners; Anti-imperialist movements -- United States; Elections -- United States -- 1900.; Exhibitions -- Illinois -- Chicago; Imperialism; Medicine -- Practice -- History -- 19th century; Medicine -- Practice -- Europe; Presidents -- United States -- Election -- 1900.; South African War, 1899-1902.; Spanish-American War, 1898 -- Philippines; Boston (Mass.) -- History; Europe -- Description and travel; Great Britain -- Colonies -- Africa; Philippines -- Foreign relations -- United States; United States -- Colonial question; United States -- Foreign relations -- Philippines; United States -- Politics and government -- 1897-1901.; United States -- Territorial expansion; Authors; Editors; Poets